The dilemma of water, food, and greener energy nexus: A novel context of COP27 for G20 economies - He, Kang; Shahzadi, Irum [UNESP]; Khan, Salahuddin; Mentel, Grzegorz; Tarczyński, Waldemar (Wiley, 2024)
In the contemporary world, achieving sustainable food production has become an urgent task for the international community and policymakers due to the rapidly growing social challenges of mankind. Sustainable food production practices aid countries in adapting to the challenges posed by climate change, thereby ensuring a better and more sustainable future for all. This study examines the impact of land use, energy efficiency (ENE), water productivity (WP), renewable energy consumption (REC), and gross domestic product (GDP) on sustainable food production in G20 nations over the period of 1998–2020. We use quantile regression approaches to capture potential heterogeneity across various food value-added distribution quantiles. The results show that arable land, WP, GDP, ENE, and REC are important factors affecting food value added in G20 nations. However, the nature of the relationship varies across different quantiles, suggesting heterogeneity in the relationships. The results show that ENE, renewable energies, and GDP are positively related to food production. However, arable land and WP are negatively related to food production. The findings can assist policymakers and stakeholders in making informed decisions to increase value added in the agricultural sector while promoting resilience and sustainability.
Keywords: arable land; food production; G-20 nations; quantile regression; renewable energy; sustainability